Bone marrow transplant with post‐transplant cyclophosphamide for recessive dystrophic epidermolysis bullosa expands the related donor pool and permits tolerance of nonhaematopoietic cellular grafts. (1st December 2019) - Ebens, C.L.; McGrath, J.A.; Tamai, K.; Hovnanian, A.; Wagner, J.E.; Riddle, M.J.; Keene, D.R.; DeFor, T.E.; Tryon, R.; Chen, M.; Woodley, D.T.; Hook, K.; et al.
Summary: Background: Recessive dystrophic epidermolysis bullosa (RDEB) is a severe systemic genodermatosis lacking therapies beyond supportive care for its extensive, life‐limiting manifestations. Objectives: To report the safety and preliminary responses of 10 patients with RDEB to bone marrow transplant (BMT) with post‐transplant cyclophosphamide (PTCy BMT) after reduced‐intensity conditioning with infusions of immunomodulatory donor‐derived mesenchymal stromal cells (median follow‐up 16 months). Methods: BMT toxicities, donor blood and skin engraftment, skin biopsies, photographic and dynamic assessments of RDEB disease activity were obtained at intervals from pre‐BMT to 1 year post‐BMT. Results: Related donors varied from haploidentical ( n = 6) to human leucocyte antigen (HLA)‐matched ( n = 3), with one HLA‐matched unrelated donor. Transplant complications included graft failure ( n = 3; two pursued a second PTCy BMT), veno‐occlusive disease ( n = 2), posterior reversible encephalopathy ( n = 1) and chronic graft‐versus‐host disease ( n = 1; this patient died). In the nine ultimately engrafted patients, median donor chimerism at 180 days after transplant was 100% in peripheral blood and 27% in skin. Skin biopsies showed stable ( n = 7) to improved ( n = 2) type VII collagen protein expression by immunofluorescence and gain of anchoring fibril components ( n = 3) by transmission electron microscopy. Early signs of clinical response include trends toward reduced body surface area of blisters/erosions from a median of 49·5% to 27·5% at 100 days after BMT ( P = 0·05), with parental measures indicating stable quality of life. Conclusions: PTCy BMT in RDEB provides a means of attaining immunotolerance for future donor‐derived cellular grafts (ClinicalTrials.gov identifier NCT02582775). What's already known about this topic? Severe, generalized recessive dystrophic epidermolysis bullosa (RDEB) is marked by great morbidity and early death. No cure currently exists for RDEB. Bone marrow transplant (BMT) is the only described systemic therapy for RDEB. What does this study add? The first description of post‐transplant cyclophosphamide (PTCy) BMT for RDEB. PTCy was well tolerated and provided excellent graft‐versus‐host disease prophylaxis, replacing long courses of calcineurin inhibitors in patients receiving human leucocyte antigen‐matched sibling BMT. What is the translational message? The PTCy BMT platform permits identification of a suitable related donor for most patients and for subsequent adoptive transfer of donor nonhaematopoietic cells after establishment of immunological tolerance.